2016
DOI: 10.1002/bjs.10090
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of drain amylase content on postoperative day 1 as a predictor of pancreatic fistula following pancreatic resection

Abstract: Background: Drain amylase content in the days immediately after major pancreatic resection has

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 52 publications
(133 reference statements)
4
79
1
Order By: Relevance
“…24 First, prolonged drainage could serve as a pathway for retrograde infection-a process that could potentially transform a benign fluid collection into an abscess. 16 In the current study, patients with a POD 1 DFA >5,000 U/L had their drains removed at the surgeon's discretion given the elevated CR-POPF risk that is associated with this scenario. 3 Although these are attractive notions, it must be emphasized that the actual mechanism remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 First, prolonged drainage could serve as a pathway for retrograde infection-a process that could potentially transform a benign fluid collection into an abscess. 16 In the current study, patients with a POD 1 DFA >5,000 U/L had their drains removed at the surgeon's discretion given the elevated CR-POPF risk that is associated with this scenario. 3 Although these are attractive notions, it must be emphasized that the actual mechanism remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study by Kawai et al 13 reported lower rates of abdominal complications and pancreatic fistula following early drain removal. 15,16 Within this subgroup, early drain removal was associated with significantly a fewer postoperative complications, including CR-POPF. 15,16 Within this subgroup, early drain removal was associated with significantly a fewer postoperative complications, including CR-POPF.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Several surgeons have stated that the reason for these conflicting results is the lack of an ideal technique that is applicable for all patients. Many investigations have been made in an attempt to reduce the rate of POPF after pancreatoduodenectomy. Consequently, several risk factors for POPF have been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…As the luminal content of the small intestine has a high level of amylase, we wished to measure its level in drain fluid as a biomarker of AL. Estimation of drain amylase has been employed in oesophagectomy and pancreatic surgery to detect anastomotic leaks early . Lee et al .…”
Section: Introductionmentioning
confidence: 99%